A2 milk and its importance in dairy production and global market - Bodnár, Ákos; Hajzser, Adél; Egerszegi, István; Póti, Péter; Kuchtík, Jan; Pajor, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
Hot topic in the dairy industry today is the growing popularity of A2 beta-casein milk among consumers and dairy farmers. Milk consists of water, lactose, fat, milk proteins, minerals and miscellaneous. The main milk proteins are caseins. The main types of caseins are alpha-casein, beta-casein, kappa-casein and moreover, the milk protein contains amino acids, peptides. The A1 and A2 beta casein variants are differ only in one amino acid because of a mutation in the 67th position. In preliminary research, A1 and A2 milk proteins have been shown to behave differently during the digestive process due to an amino acid variation. The A1 β-casein amino acid chain is susceptible to breakdown during normal enzymatic digestion, the peptide it breaks down to is a bioactive opioids; beta-casomorphins (BCM), one of peptides, BCM7 has been widely studied. A2 β-casein’s amino acid chain is not as likely to experience this breakdown into BCM7 (Clarke, 2014). This study is a short summary about the previous researches and basic information about A2 milk production. In Hungary, there is a farm with 200 dairy cattle and good genetic background. This dairy farm have started to select and test their animals for A2 milk production.
Keywords: A2 milk; BCM7; cattle breeds